2015
DOI: 10.1007/s10096-015-2511-x
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy-based identification of nosocomial outbreaks of the clonal bacterium Escherichia coli

Abstract: DNA-based techniques are frequently used to confirm the relatedness of putative outbreak isolates. These techniques often lack the discriminatory power when analyzing closely related microbes such as E. coli. Here the value of Raman spectroscopy as a typing tool for E. coli in a clinical setting was retrospectively evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Recent reports have suggested that Raman spectroscopy is useful for rapidly detecting and classifying microbes [11,[13][14][15][16]. Raman spectroscopy is a label-free optical sensing technology based on the inelastic scattering of light by molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have suggested that Raman spectroscopy is useful for rapidly detecting and classifying microbes [11,[13][14][15][16]. Raman spectroscopy is a label-free optical sensing technology based on the inelastic scattering of light by molecules.…”
Section: Introductionmentioning
confidence: 99%
“…14,[18][19][20][21] While NIR based applications have had great success differentiating clonal isolates of E. coli and K. pneuomoniae, none have considered a large dataset of different Enterobacteriaceae. [22][23][24] In this study, 16 clinically relevant Enterobacteriaceae strains, from 8 different genera were studied with Raman spectroscopy. Two Raman spectroscopic methods were compared: SC-RMS and FP-RS on colonies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, discriminating between similar microbes, such as quinolone‐nonsusceptible E . coli ST131:O25b and ST1193:O75, is difficult (Kusters et al, ). Also, E .…”
Section: Introductionmentioning
confidence: 99%
“…This spectroscopic method provides multiple spectral peaks indicating distinct vibration modes of specific scattering molecules related to various biochemical components such as DNA, RNA, protein, lipids, and carbohydrates (Choi et al, ). Some studies have suggested that Raman spectroscopy could be used for rapidly detecting and classifying microbes (Jung et al, ; Kusters et al, ). Willemse‐Erix et al () reported that Raman spectroscopy detected 95% of Klebsiella pneumoniae isolates and 97% of E. coli isolates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation